What Drives US Foreign Borrowing? Evidence on the External Adjustment to Transitory and Permanent Shocks - Corsetti, Giancarlo; Konstantinou, Panagiotis Th (American Economic Review, 2012)
The joint dynamics of US net output, consumption, and (the market value of) foreign assets and liabilities, characterized empirically following Lettau and Ludvigson (2004), is shown to be consistent with current account theory. US consumption is virtually insulated from transitory shocks, while these contribute to variations in net output and gross foreign positions—consumption is smoothed against temporary fluctuations in returns. A single permanent shock—naturally interpreted as a supply shock—raises consumption swiftly while causing net output to adjust gradually. This leads to persistent, procyclical external deficits, while moving gross assets and liabilities in the same direction. JEL: E21, E23, F32, F34